Amiodarone-induced thyroid dysfunction in children: insights from the THYRAMIO study - Sarah Montenez; Stéphane Moniotte; Annie Robert; Lieven Desmet; Philippe A. Lysy (Therapeutic Advances in Endocrinology and Metabolism, 2021)
Background: Amiodarone treatment is effective against various types of arrhythmias but is associated with adverse effects affecting, among other organs, thyroid function. Amiodarone-induced thyroid dysfunction was not thoroughly evaluated in children as it was in adults, yet this affection may lead to irreversible neurodevelopmental complications. Our study aimed to define the incidence and risk factors of amiodarone-induced thyroid dysfunction in children. Methods: The study was designed as an observational study with a retrospective clinical series of 152 children treated by amiodarone in the Pediatric Cardiology Unit of our center from 1990 to 2019. All patients were divided into three groups according to their thyroid status: euthyroid, AIH (amiodarone-induced hypothyroidism) or AIT (amiodarone-induced thyrotoxicosis). Patients from these three groups were compared in terms of key clinical and therapeutic features. Results: Amiodarone-induced thyroid dysfunction was present in 23% of patients. AIT (5.3%) was three times less common than AIH (17.7%), and its occurrence increased with older age ( p  < 0.05), treatment dosage ( p  < 0.05), treatment duration ( p  < 0.05) and the number of loading doses administered ( p  < 0.05). There were no distinctive clinical features between euthyroid and AIH groups. A multivariable prediction model of AIT was built, with a yield of 66.7% as positive predictive value and 96.7% as negative predictive value. Conclusion: We observed that one in five children developed amiodarone-induced thyroid dysfunction. Special attention is required for older children with a high dosage and long-term therapy and who received a large number of loading doses, since these children are at risk to develop AIT, which is more delicate to manage than AIH.